Valorization of passion fruit: development, characterization and optimization of biodegradable edible films - Maria Clara Coutinho Macedo; Viviane Dias Medeiros Silva; Camila Gonçalves Rodrigues; Débora Tamires Vitor Pereira; Maria Aparecida Vieira Teixeira Garcia; Christiano Vieira Pires; Camila Argenta Fante (Polímeros)
Abstract This work aimed to develop biodegradable films from yellow passion fruit (Passiflora edulis f. flavicarpa) peel flour. The Central Composite Rotational Design was used in a total of 11 tests, in which the independent variables were the concentrations of starch and glycerol, characterized with regard to physical, mechanical and barrier properties. The films were classified as soluble and showed low permeability to water vapor. The tensile strength, elastic modulus and deformation rate were directly related to the concentration of starch and glycerol. The film of test 7 had the best characterization results; therefore, it was analyzed for biodegradability. As for biodegradability, the film obtained an average mass loss of 92.77 ± 4.28%, being a great alternative to the use of non-biodegradable polymers. The films showed acceptable degree of plasticization, which was favored by intermolecular interactions between the components of the flour, starch and glycerol.